2018
DOI: 10.5897/ajmr2017.8757
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic susceptibility and serotype patterns of Pseudomonas aeruginosa from clinical isolates in Abidjan, Cote dIvoire

Abstract: Pseudomonas aeruginosa (P. aeruginosa) has been found to be a common hospital acquired pathogen, responsible for several severe infections. The objective of this study was to describe the antibiotic resistance profile of P. aeruginosa strains from human sample. This descriptive study was carried out on 168 isolated strains of P. aeruginosa collected from January 2014 to December 2015 at the Pasteur Institute of Côte d'Ivoire. The strains identification was done according to the methods of conventional bacterio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
1

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 10 publications
0
1
1
Order By: Relevance
“…Analysis of antibiogram revealed the association of MDR isolates with serotypes O6, O10 and O11. Previous studies reported prevalence of MDR P. aeruginosa among serotype O11[33] [38] [39] [40]. In contrast to our results, Aydoğan et al found association of susceptibility to all drugs and serotypes (O6, O11) and MDR was common among serotype O12 which was not detected in S. H. Abdel-Rhman, D. E. Rizk DOI: 10.4236/aim.2018.88042 633 Advances in Microbiology…”
contrasting
confidence: 97%
See 1 more Smart Citation
“…Analysis of antibiogram revealed the association of MDR isolates with serotypes O6, O10 and O11. Previous studies reported prevalence of MDR P. aeruginosa among serotype O11[33] [38] [39] [40]. In contrast to our results, Aydoğan et al found association of susceptibility to all drugs and serotypes (O6, O11) and MDR was common among serotype O12 which was not detected in S. H. Abdel-Rhman, D. E. Rizk DOI: 10.4236/aim.2018.88042 633 Advances in Microbiology…”
contrasting
confidence: 97%
“…Hafez et al [31] and Mohammed [32] reported O12 among the commonest serotypes detected. A study conducted by Elogne et al [33] in Abidjan and Cattoen et al [34] in Tunisia reported O4 as the most prevalent serotype. This may be attributed to the difference in specimen type and geographical location.…”
Section: Discussionmentioning
confidence: 99%